PERAN LITERASI KEUANGAN SEBAGAI PREDIKTOR KINERJA DAN KEBERLANJUTAN UMKM - DEWA AYU RUMINI; A.A. MEDIA MARTADIANI; A.A.BAGUS AMLAYASA (AKADEMIKA, 2020)
The MSME sector has an important role for the economic development of a country, especially in encouraging Indonesia's economic growth. But in practice, SMES often experience delays in development, so that the potential of SMES has not been completed optimally. Many factors as a predictor of SMES performance and sustainability, in this research used financial literacy as a predictor of SMES performance and sustainability in Badung Regency. This research uses quantitative approaches using primary data through questionnaires. The respondents in this study were 100 MSMES in Badung Regency. The variables used in this study were financial literacy as independent variables, as well as MSMES and MSME sustainability as dependent variables. The method used in analyzing data is Structural Equation Modeling (SEM). The results showed that financial literacy has a positive and significant impact on SMES performance and SMES sustainability in Badung Regency.